From Pausanias to Baedeker and Trip Advisor: Textual proto-tourism and the engendering of tourism distribution channels - Katsoni, Vicky; Fyta, Anna (Turyzm/Tourism, 2021)
The key aim of this article is to provide an interdisciplinary look at tourism and its diachronic textual threads bequeathed by the ‘proto-tourist’ texts of the Greek travel author Pausanias. Using the periegetic, travel texts from his voluminous Description of Greece (2nd century CE) as a springboard for our presentation, we intend to show how the textual strategies employed by Pausanias have been received and still remain at the core of contemporary series of travel guides first authored by Karl Baedeker (in the 19th century). After Baedeker, Pausanias’ textual travel tropes, as we will show, still inform the epistemology of modern-day tourism; the interaction of travel texts with travel information and distribution channels produces generic hybrids, and the ancient Greek travel authors have paved the way for the construction of networks, digital storytelling and global tourist platforms.